2019
DOI: 10.3126/gaze.v10i1.22778
|View full text |Cite
|
Sign up to set email alerts
|

Medical Tourism and Hospitality in Hospital

Abstract: Medical tourism is a growing phenomenon with policy implications for health systems, particularly of destination countries. Both private sectors and the governments of such destinations are found playing important role for medical tourism promotion and development. This study tries to highlight a conceptual analysis of medical tourism, the targeting of medical tourism flows and major destinations, and the proposed medical tourism development strategies based on the experience of several countries regarding med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(73 reference statements)
0
4
0
1
Order By: Relevance
“…Wellness tourism is umbrella term under which all other tourism incorporate. Wellness tourism is defi ned by Smith and Puczko (2014; in Kunwar, 2019) as 'trips aiming at a state of health where the main domains of wellness (body, mind, spirit) are harmonized or balanced. Th ere is emphasis on prevention rather than cure, but some medical treatment may be used to lifestyle based therapies. '…”
Section: Spiritual Tourismmentioning
confidence: 99%
“…Wellness tourism is umbrella term under which all other tourism incorporate. Wellness tourism is defi ned by Smith and Puczko (2014; in Kunwar, 2019) as 'trips aiming at a state of health where the main domains of wellness (body, mind, spirit) are harmonized or balanced. Th ere is emphasis on prevention rather than cure, but some medical treatment may be used to lifestyle based therapies. '…”
Section: Spiritual Tourismmentioning
confidence: 99%
“…To better understand the concept of medical tourism, it is important to recognize the interrelationship between medical tourism and hospitality in hospitals. Stakeholders in the system need to be aware of the significance of cross-cultural behavior and intercultural communication between host and patient (Kunwar, 2019). conducted research on medical tourism in developing countries and revealed the relationship between medical services and tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, global interest in traditional medicine has increased (Dawn & Pal, 2011;Kunwar, 2019) and Ayurveda is recognized as traditional Indian medicine (Patwardhan et.al., 2005). The modern epidemiological transition has allowed the growth of the conventional system of medicine International Journal Health Management and Tourism https://dergipark.org.tr/tr/pub/ijhmt across the world (Gupta et.al., 2015) and traveling across borders to receive high-tech health care is increasing (Dawn & Pal, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hotelaria hospitalar é muito mais do que a administração dos leitos de um hospital, mas é também a coordenação de setores como lavanderia, recepção, higienização e resíduos. No entanto, para Kunwar (2019), embora as palavras hospital e hospitalidade tenham a mesma raiz, alguns hospitais têm sido vistos como locais não muito hospitaleiros. Em função disso, cabe ressaltar que de acordo com Diniz e Bueno (2020), há uma lacuna científica na área de hotelaria hospitalar, que merece atenção de pesquisadores de campos afins.…”
Section: Introductionunclassified